The Cyclic Universe A Conversation with Roger Penrose. - Burton, Howard (Ideas Roadshow Conversations Ser., 2013)
In the last twenty years, cosmology has unexpectedly emerged as one of the most exciting and dynamic fields of modern science. From astoundingly precise measurements of the cosmic microwave background to the ongoing mysteries of dark energy and dark matter, modern cosmology is unquestionably in the midst of its Golden Age. And yet, one of the most eminent mathematical physicists of our age, Roger Penrose is convinced that there is one fundamental problem that is consistently being overlooked: why did our universe begin in such a particular state of extremely low entropy? His Conformal Cyclic C.